Perceptions of leadership effectiveness in schools for children who are blind or have low vision in Nigeria. Issue 1 (2nd January 2017) - Oyinlade, A. Olu; Ajuwon, Paul M.
Abstract : This study used the standard-based essential behavioural leadership qualities (EBLQ) method of leadership assessment, to determine leadership effectiveness of the principals of the schools for children who are blind and have low vision in Nigeria, from the perspective of the teachers of these schools. The four-stage method of leadership assessment of the EBLQ method was used to analyze data ( N = 271) collected through availability sampling, to determine leadership effectiveness of the principals relative to levels of essentiality of EBLQ items. Findings show a pattern of incongruence between rankings of essentialities and effectiveness of the principals on the EBLQ items. The principals were perceived most effective in having 'excellent educational qualifications' which was ranked fourth as essential for leadership effectiveness. The principals were also rated twentieth on 'timely payment of salary', which was ranked most essential for leadership effectiveness. Overall effectiveness of the principals, however, was described as exemplary. This study is expected to contribute to much-needed studies on leadership in the schools for the blind in Nigeria, as well as provide a coaching effect for the principals of these schools.